Pengaruh Corporate Governance Dan Intensitas Modal Terhadap Firm Value Dengan Tax Planning Sebagai Pemoderasi - Putra, Robiur Rahmat; Dondoan, Gracelia Angelina (Universitas 17 Agustus 1945 Jakarta, 2021)
This study aims to find out the relationship between 4 variables of independent variables Corporate Governance (X1) and Capital Intesitas (X2) to Firm Value (Y) and Tax Planning (Z) as moderating. The population in this study was a Manufacturing Company registered in Burs Efek Indonesia (IDX) for the period 2016-2019. The data analysis tool used is using Stata. This research is a type of quantitative research. Data collection method used is secondary data that is data obtained by indirectly through intermediary media. This research data was obtained from www.idx.co.id. This research uses purposive sampling method. Based on the results of regression analysis that the author did, showed that simultaneously all variable values prop > 0.05 then can be concluded that firm value is not influenced by Corporate Governance and Capital Intensity and Tax Planning and the need for testing.Keywords: Corporate Governance, Capital Intensity, Firm Value, Tax Planning